"Senegal yewuleen!" Rap in Dakar: liminarity, protest movement and popular culture - (:unkn) unknown (My University, 2008)
Since the late 1980s, there has been the emergence and spread of a new cultural and social movement in the Senegalese capital of Dakar: hip-hop. Rap (the vocal form of hip-hop) was spread throughout Dakar by middle-class teenagers who had access to American and European tapes acquired through their relatives living as immigrants in these countries. In the beginning of the 1990s, this music was broadcast on the radio which led to an expansion of the listening audience, reaching lower-class youth in the disadvantaged suburbs of Dakar. Following fourteen months of fieldwork in Dakar and its surrounding suburbs, I tried to determine how Senegalese young people, traditionally discouraged from participating in public discourse and responsibilities in general, managed to play a determining role in the redefinition of a new Senegalese social order, both in real and symbolic terms. In a context of presidential elections and social protest, many young people ventured into this new kind of artistic expression which consisted of a progressive africanization of this western form. I wondered whether this “rap movement” matched the description of a social movement or rather was an African popular culture in an urban context. Subsequently, the main issue was first to understand how a form of African creative expression like Rap in Dakar could be involved simultaneously in cultural, social, religious and political spheres. Additionally, rappers not only offer a new interpretation of Senegalese history and tradition, but they also create new musical and language codes. They also allow for the redefinition of their relationship to the family and religion, notably Islam in the form of Sufi brotherhoods. Finally, rap's gradual movement away from an informal activity towards a professional one has tended to change its mode of creation and its opening toward the world makes rappers constantly adjust between the local and the global.
Keywords: African Research